The Wiley handbook of psychology, technology and society - Cheever, Nancy A.; Rosen, Larry D.; Carrier, L. Mark (Malden, MA : Wiley Blackwell, 2015)
'Provides analysis of the latest research on generational differences, Internet literacy, cyberbullying, sexting, Internet and cell phone dependency, and online risky behavior'--
What do the Formal Ethical Guidelines Say?Is Online Data Text or People?; Is Online Content Public or Private?; Accessing Web Content: Website Policies and Legal Considerations; How Online Researchers Can Protect the Anonymity and Confidentiality of the Researched; Social Responsibility; Conclusion; References; Part II Children, Teens, andTechnology; Chapter 7 Executive Function in Risky Online Behaviors by Adolescents and Young Adults; Executive Function; Influence of EF on Risky Online Behaviors by Youths; Two Studies on Risky Online Behaviors and EF; Results; Discussion.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Social psychology; Internet -- Social aspects; Internet -- Security measures; Internet -- Security measures; Internet -- Social aspects; PSYCHOLOGY -- Social Psychology; Social psychology; PSYCHOLOGY -- Social Psychology; Internet -- Security measures; Internet -- Social aspects; Social psychology; Electronic books